Complexity analysis of fetal heart rate preceding intrauterine demise. (August 2016) - Schnettler, William T.; Goldberger, Ary L.; Ralston, Steven J.; Costa, Madalena
Abstract: Background: Visual non-stress test interpretation lacks the optimal specificity and observer-agreement of an ideal screening tool for intrauterine fetal demise (IUFD) syndrome prevention. Computational methods based on traditional heart rate variability have also been of limited value. Complexity analysis probes properties of the dynamics of physiologic signals that are otherwise not accessible and, therefore, might be useful in this context. Objective: To explore the association between fetal heart rate (FHR) complexity analysis and subsequent IUFD. Our specific hypothesis is that the complexity of the fetal heart rate dynamics is lower in the IUFD group compared with controls. Study design: This case-control study utilized cases of IUFD at a single tertiary-care center among singleton pregnancies with at least 10 min of continuous electronic FHR monitoring on at least 2 weekly occasions in the 3 weeks immediately prior to fetal demise. Controls delivered a live singleton beyond 35 weeks' gestation and were matched to cases by gestational age, testing indication, and maternal age in a 3:1 ratio. FHR data was analyzed using the multiscale entropy (MSE) method to derive their complexity index. In addition, pNN x, a measure of short-term heart rate variability, which in adults is ascribable primarily to cardiac vagal tone modulation, was also computed. Results: 211 IUFDs occurred during the 9-year period of review, but only 6 met inclusion criteria. The median gestational age at the time of IUFD was 35.5 weeks. Three controls were matched to each case for a total of 24 subjects, and 87 FHR tracings were included for analysis. The median gestational age at the first fetal heart rate tracing was similar between groups (median [1st–3rd quartiles] weeks: IUFD cases: 34.7 (34.4–36.2); controls: 35.3 (34.4–36.1); p = .94). The median complexity of the cases' tracings was significantly less than the controls' (12.44 [8.9–16.77] vs. 17.82 [15.21–22.17]; p < .0001). Furthermore, the cases' median complexity decreased as gestation advanced whereas the controls' median complexity increased over time. However, this difference was not statistically significant [−0.83 (−2.03 to 0.47) vs. 0.14 (−1.25 to 0.94); p = .62]. The degree of short-term variability of FHR tracings, as measured by the pNN metric, was significantly lower ( p < .005) for the controls (1.1 [0.8–1.3]) than the IUFD cases (1.3 [1.1–1.6]). Conclusions: FHR complexity analysis using multiscale entropy analysis may add value to other measures in detecting and monitoring pregnancies at the highest risk for IUFD. The decrease in complexity and short-term variability seen in the IUFD cases may reflect perturbations in neuroautonomic control due to multiple maternal-fetal factors.